Synergistic effects of chlorination and photoaging on tire related particles aging and tetracycline adsorption: Experimental and molecular dynamics insights - Huan Tang; Jiao Wu; Beichen Yang; Zhen Li; Yue Yin; Tinglin Huang; Gang Wen; Baoshan Xing (Journal of Hazardous Materials, 2026)

Highly efficient single-layer color-tunable QLEDs enables by the real-time interface exciplex modulation with AgInZnS QDs - Tianjun Hu; Xiuting Wu; Qingsong Shan; Xingxing Duan; Xiaoyue Cai; Mengjin Huang; Junhui Dai; Hong Zhong; Beichen Yuan; Hengyang Xiang; Linxiang Yang; Qiangyu Dai; et al. (Science Bulletin, 2026)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Temperature response of magnetic susceptibility and pore structure of white Bleached sandstone - Beichen Du; Jishi Geng; Qiang Sun; Xin Hu; Hao Huang; Pengda Ma; Pengfei Li (Journal of Applied Geophysics, 2025)

Effect of pH and salinity on the release of polystyrene microplastics derived dissolved organic matter as revealed by experimental studies and molecular dynamic simulations - Yue Yin; Zhen Li; Ruotong Li; Beichen Yang; Tinglin Huang; Huan Tang (Science of The Total Environment, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Enhanced fucoxanthin and biomass accumulation in Phaeodactylum tricornutum by combined effect of two plant hormones - Jiaxue Lin; Shaogeng Zhao; Beichen Huang; Jianhua Yin; Shengjie Li; Yan Ma; Jingrun Ye; Haiying Wang; Xiaofeng Ji; Jiakun Xu; Zhipeng Wang (Food Bioscience, 2024)

High-sensitive determination of tetracycline antibiotics adsorbed on microplastics in mariculture water using pre-COF/monolith composite-based in-tube solid phase microextraction on-line coupled to HPLC-MS/MS - Jinling Pang; Hongzhe Chen; Huige Guo; Kunning Lin; Shuyuan Huang; Beichen Lin; Yuanbiao Zhang (Journal of Hazardous Materials, 2024)

Zero-valent iron in phosphate removal: Unraveling the role of particle size and dissolved oxygen - Shiteng Feng; Beichen Zhang; Jingshu Wang; Jinhui Jeanne Huang (Journal of Water Process Engineering, 2024)

Study of a Center Pipe Oscillating Column Wave Energy Converter Combined with a Triboelectric Nanogenerator Device - Yan Huang; Shaohui Yang; Jianyu Fan; Zhichang Du; Beichen Lin; Yongqiang Tu; Lei Pan (Journal of Marine Science and Engineering, 2024)
Wave energy is one of the most widely distributed and abundant energies in the ocean, and its conversion technology has been broadly researched. In this paper, a structure that combines a traditional center pipe oscillating water column and a triboelectric nanogenerator is proposed. Firstly, the structural characteristics and geometric parameters of the device are designed. The working process of the device is introduced, the motion equation of the device is established, and the power generation principle of the triboelectric nanogenerator is deduced and analyzed theoretically. Secondly, hydrodynamic modeling and simulation are carried out, the influence of the bottom shape of the main floating body and the structural parameters of the sag plate on the hydrodynamic force of the device is analyzed, and an electric field simulation of the generation process of the friction nanogenerator is carried out. Finally, experiments involving the wave water tank of the proposed device are conducted, including charging the capacitor of the device under different wave conditions and directly lighting the LED lamp. The performance of the proposed device under different wave conditions is discussed. According to the test results, the feasibility of the proposed device for wave energy conversion is confirmed.

The roles of different Fe-based materials in alleviating the stress of Cr(VI) on anammox activity: Performance and mechanism - Beichen Zhang; Jingshu Wang; Shiteng Feng; Jinhui Jeanne Huang; Xiaoyu Han (Chemical Engineering Journal, 2023)

Distinct Assembly Mechanisms for Prokaryotic and Microeukaryotic Communities in the Water of Qinghai Lake - Mingxian Han; Jianrong Huang; Jian Yang; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Journal of Earth Science, 2023)

Microbial carbon fixation and its influencing factors in saline lake water - Jianrong Huang; Jian Yang; Mingxian Han; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Science of The Total Environment, 2023)

Molecular level insight into the different interaction intensity between microplastics and aromatic hydrocarbon in pure water and seawater - Wenjin Liu; Huan Tang; Beichen Yang; Chenyang Li; Ying Chen; Tinglin Huang (Science of The Total Environment, 2023)

Molecular characterization and expression of the SiUCP2 gene in sea urchin Strongylocentrotus intermedius - Lingshu Han; Zijiao Quan; Bing Han; Beichen Ding; Xiaofang Huang; Heng Wang; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)

Mechanical Properties and Failure Behavior of Dry and Water-Saturated Anisotropic Coal Under True-Triaxial Loading Conditions - Yubing Liu; Guangzhi Yin; Minghui Li; Dongming Zhang; Gun Huang; Peng Liu; Chao Liu; Honggang Zhao; Beichen Yu (Rock Mechanics and Rock Engineering, 2020)